Manajemen Konflik Dalam Organisasi Masyarakat Pendekatan Dan Praktik Dalam Konteks Islam - Fidyah Apriliani Fidori; Himmatut Taqiyah; Ayyul Fariqoini; Mualimin Mualimin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Conflicts within community organizations are common, particularly in multicultural environments. This article explores conflict management approaches rooted in Islamic values such as syura (consultation), ishlah (reconciliation), and afw (forgiveness) through a literature review. The findings reveal that Islamic principles are effective in resolving conflicts and fostering social harmony, supported by Islamic leadership characterized by shiddiq (integrity) and amanah (trustworthiness). While these approaches are highly relevant, challenges such as limited understanding and leadership capacity highlight the need for further strengthening and development.